Effects of antioxidant vitamin supplementation on sports performance, endurance and strength performance: a systematic review and meta-analysis - Dadalt, E. K.; Stefani, G. P. (Sport Sciences for Health, 2024)
Supplementation with antioxidant vitamins is common among amateur and elite athletes. It is thought to cause a reduction in the muscle damage that results from exercised-induced oxidative stress, increasing the ability to improve performance markers. A systematic review and meta-analysis were carried out to evaluate the effects of supplementation with antioxidant vitamins (A, C, and E), alone and/or combination of sports performance (maximum oxygen consumption, maximum strength) in athletic populations. Eligibility criteria included only randomized clinical trial studies written in English, Spanish and Portuguese with no restriction on the year of publication. Case studies, observational studies, quasi-experimental trials, literature reviews, and animal studies were excluded from this systematic review. Eligible studies were searched on PubMed/Medline, Web of Science, SciElo, and Google Scholar. To minimize the risk of publication bias, searches were also conducted in the grey literature. Database searches occurred from June to September of 2022. Thirteen randomized controlled trials with a total of 398 participants. The risk of bias was assessed and presented low overall quality. In general, markers of sports performance and overall performance were not affected by antioxidant vitamin supplementation (SMD = 0.00, 95%CI - 0.43, 0.20, P = 0.98). Similarly, evaluations of aerobic resistance (SMD = - 0.06, 95%CI - 0.31, 0.19, P = 0.66) as well as muscle strength (SMD = 0.04, 95% CI - 0.31, 0.39, P = 0.81) were not influenced by supplementation. Thus, the results of this meta-analysis of clinical trials demonstrate that supplementation with isolated and/or combined antioxidant vitamins is not associated with improved sports performance.